2015
DOI: 10.1186/s12891-015-0725-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy vs. internet-based exercise training (PATH-IN) for patients with knee osteoarthritis: study protocol of a randomized controlled trial

Abstract: BackgroundPhysical activity improves pain and function among individuals with knee osteoarthritis (OA), but most people with this condition are inactive. Physical therapists play a key role in helping people with knee OA to increase appropriate physical activity. However, health care access issues, financial constraints, and other factors impede some patients from receiving physical therapy (PT) for knee OA. A need exists to develop and evaluate other methods to provide physical activity instruction and suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
(53 reference statements)
0
35
0
4
Order By: Relevance
“…The third study examined PhysicAl THerapy vs INternet Based Exercise Training for Patients with Knee OA (PATH-IN); this study primarily involved patients receiving care within the University of North Carolina (UNC) healthcare system, with 2% enrolled from the surrounding community with various sources of healthcare. Details of the study protocols have been described previously (16, 17). Briefly, in the PRIMO-Duke cluster randomized trial, the clinics were randomized to Provider Intervention or Control, and then study participants within those clinics were assigned to Patient Intervention or Control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third study examined PhysicAl THerapy vs INternet Based Exercise Training for Patients with Knee OA (PATH-IN); this study primarily involved patients receiving care within the University of North Carolina (UNC) healthcare system, with 2% enrolled from the surrounding community with various sources of healthcare. Details of the study protocols have been described previously (16, 17). Briefly, in the PRIMO-Duke cluster randomized trial, the clinics were randomized to Provider Intervention or Control, and then study participants within those clinics were assigned to Patient Intervention or Control.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were included in the studies if they had: a diagnosis of hip OA (PRIMO-Duke and PRIMO-VA) or knee OA (PRIMO-Duke, PRIMO-VA, and PATH-IN), based on either radiographic evidence in the electronic medical record or American College of Rheumatology clinical criteria (18), along with current symptoms in the joint(s) with OA(16, 17). Participants in all studies were not meeting US Department of Health and Human Services physical activity recommendations(19), and participants in the PRIMO-Duke and PRIMO-VA studies also had a body mass index (BMI) ≥ 25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knee osteoarthritis (KOA) is a common knee degenerative disease characterized by cartilage degeneration, cartilage exfoliation, and subchondral bone hyperplasia, leading to knee pain, joint instability and functional limitations [1]. KOA severely affects patients' quality of life and is a major public health issue [2]. An epidemiological survey published in Proceedings of the National Academy of Sciences (PNAS) showed that the incidence of KOA in the U.S. population has doubled since the mid-twentieth century [3].…”
Section: Introductionmentioning
confidence: 99%
“…La OA está incluida entre las principales causas de discapacidad 3,4 . Según la OMS 4 , cerca de Dada la alta prevalencia de estas afecciones, el grado de discapacidad que pueden generar y los gastos sanitarios relacionados, la presente investigación tiene como objetivo realizar una intervención en los pacientes afectados con OA para valorar la efectividad del programa de tratamiento kinesiológico, destacando así las ventajas que ofrece con respecto a otras técnicas [14][15][16] .…”
Section: Introductionunclassified